Short-Chain Fatty Acids Alleviate Hepatocyte Apoptosis Induced by Gut-Derived Protein-Bound Uremic Toxins - Deng, Mingjuan; Li, Xingqi; Li, Weiwei; Gong, Jiahui; Zhang, Xiaoying; Ge, Shaoyang; Zhao, Liang (Frontiers in Nutrition, 2021)
Chronic kidney disease (CKD) is characterized with influx of uremic toxins, which impairs gut microbiome by decreasing beneficial bacteria that produce short chain fatty acids (SCFA) and increasing harmful bacteria that produce gut-derived protein-bound uremic toxins (PBUTs). This study aimed to assess the pro-apoptotic effects of three major gut-derived PBUTs in hepatocytes, and effects of SCFA on apoptosis phenotype in vitro. HepG2 (human liver carcinoma cells) and THLE-2 (immortalized human normal liver cells) cell line were incubated with 0, 2, 20, 200, 2000 µM p-cresol sulfate (PCS), indoxyl sulfate (IS), and hippuric acid (HA) respectively for 24 h. Flow cytometry analysis indicated that three uremic toxins induced varying degrees of apoptosis in hepatocytes and HA represented highest efficacy, further confirmed by western blot of apoptosis protein expression (Caspase-3, Caspase-9, Bcl-2 and Bax). Human normal hepatocytes (THLE-2) are more sensitive to PBUTs-induced apoptosis compared with human hepatoma cells (HepG2). Mechanistically, extracellular HA could enter hepatocytes, increase ROS generation and decrease mitochondrial membrane potential dose-dependently in THLE-2 cells. Notably, coculture with SCFAs (acetate, propionate, butyrate) for 24h significantly improved HA-induced apoptosis in THLE-2 cells, and propionate (500 µM) represented highest efficacy. Propionate reduction of apoptosis was associated with improving mitochondria dysfunction and oxidative stress in a manner involving reducing Caspase-3 expression, ROS production, and increasing Bcl-2/Bax level. As such, our studies validated PBUTs accumulation might be an important cause of liver dysfunction in CKD patients, and supplementation of SCFAs might be a viable way to protect liver for CKD patients.